2014
DOI: 10.1371/journal.pone.0099825
|View full text |Cite
|
Sign up to set email alerts
|

ClinicalCodes: An Online Clinical Codes Repository to Improve the Validity and Reproducibility of Research Using Electronic Medical Records

Abstract: Lists of clinical codes are the foundation for research undertaken using electronic medical records (EMRs). If clinical code lists are not available, reviewers are unable to determine the validity of research, full study replication is impossible, researchers are unable to make effective comparisons between studies, and the construction of new code lists is subject to much duplication of effort. Despite this, the publication of clinical codes is rarely if ever a requirement for obtaining grants, validating pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
190
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 162 publications
(202 citation statements)
references
References 29 publications
(37 reference statements)
1
190
0
2
Order By: Relevance
“…The READ codes used in this study are available from the Clinical Codes repository (www. clinicalcodes.org) [24]. We examined the electronic health records of the included individuals to determine the presence of foot ulcers occurring after 1 January 2004 using the relevant READ codes.…”
Section: Methodsmentioning
confidence: 99%
“…The READ codes used in this study are available from the Clinical Codes repository (www. clinicalcodes.org) [24]. We examined the electronic health records of the included individuals to determine the presence of foot ulcers occurring after 1 January 2004 using the relevant READ codes.…”
Section: Methodsmentioning
confidence: 99%
“…27 Another UK based study of primary care data from The Health Improvement Network (THIN) found that the intentional incidence of poisoning in females aged 15-17 years increased from 39.1 to 46.6 per 10 000 person years between the two successive calendar periods, 1992-96 to 2007-12. 25 Recent data from the adult psychiatric morbidity survey in England, 28 based on clinical interviews, indicate that 11.7% of [16][17][18][19][20][21][22][23][24] year old females in 2007 reported ever self harming, increasing to 19.7% in 2014. In a multicentre hospital based study in England, 26 age standardised incidence of self harm appeared to decline from 2000 until 2009, with a possible increase and stabilising of rates from 2009 to 2012, although figures were based on a combined age range of 15-24 years.…”
Section: Temporal Trends In Sex and Age Specific Incidencementioning
confidence: 99%
“…We included age, sex, number of general practitioner consultations, and having had a previous emergency hospital admission in 2010-2012. We also included the following morbidities measured before April 2012 (presence of each diagnosis was ascertained using published clinical code lists as collected in the Manchester Clinical Codes repository 27 ): epilepsy, 28 chronic renal disease, 29 cancer, 30 asthma, 29 stroke, 31 coronary heart disease, 31 diabetes, 31 chronic obstructive pulmonary disease, 28 depression, 32 and schizophrenia. 32 Furthermore, we took into account clustering at the practice level 33 : we included practice-level information including deprivation, location (conurbation, urban, rural), and estimated the number of general practitioners in a practice ascertained from consultations and staff role information.…”
Section: Measures Of Confounding Variablesmentioning
confidence: 99%